The Role of Tourism in Planning the Smart City - La Rocca, Rosa Anna (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The article starts from the consideration that tourism, for the size it has assumed and for its role in the economies, can be considered an "urban phenomenon"; as such, it needs adequate governance processes, politics and tools in order to reduce impacts on the organization of cities and urban livability in general. The emerging paradigm of “Smart City” is an opportunity to reconsider the current mechanisms of government and planning of the cities, but it needs a holistic approach that goes beyond the one applied per parts that still seems to prevail in the declination of the components of urban smartness (economy, mobility, environment, people, living, governance). At present, the technological component seems to prevail probably due to the ease of diffusion of the instruments, rather than an innovation of the processes. Promotion initiatives seems to concentrate exclusively on the city branding, rather than on initiatives to make cities able to support an additional urban load expressed by the tourism demand. Yet, potentialities of the application of new technologies could strengthen the decisional role in defining adequate urban policies to manage urban tourism and to optimize urban supply of services and facilities. However, at present, urban smartness for tourism seems to be concentrated on the amount of apps available to enhance the use of specific resources or, more rarely, of the urban mobility systems. Both the “big data” and the “open data” revolution, in Italy, do not yet seem to have achieved the hoped results, and the availability of data to allow appropriate management actions, is still one of the main difficulties for those involved in the analysis and quantification of the phenomenon. In addition, the numerous rankings on urban smartness refer to the prevalence of one component on the others, failing to consider the complexity of the urban system and of tourism, in particular. With these premises, the article tries to underline how tourism could be the object of urban policies and strategies aimed at reducing impacts on the city.